Strategi Peningkatan Kemampuan Peserta Didik Dalam Pembelajaran Tahfizh Al-Qur’an Di SDIT Adzkia 3 Padang - Rizka, Engla; Kenedi, Gusril; Rehani, Rehani; Ramanda, Deski (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
This research uses a qualitative research model and in this study in the form of field research using a descriptive approach. This study discusses strategies for improving students' abilities in the learning process of tahfizd Al-Qur'an at SDIT Adzkia 3 Padang. This research can be concluded that the tahfidz teaching team implements several strategies for students to be able to improve their memorization, namely carrying out tests during the selection to enter school, grouping them according to their level of memorization, using group and individual approaches in depositing memorization and the tahfidz teaching team also prepares optimally in in the form of lesson plans, monitor books and monthly report cards, using the method used by the jama' method and the technique used in the form of giving advice, prizes, games, and punishments.